Pengaruh Guided Imagery Terhadap Tingkat Kecemasan Pasien Pre-Operasi (The Effects Of Guided Imagery On Preoperative Anxiety Level) - Grace Benedikta Polii; Syenshie Virgini Wetik (Sekolah Tinggi Ilmu Kesehatan Ngesti Waluyo, 2020)
Anxiety is a reaction to psychological disorders experienced by most patients in the face of surgery. Signs and symptoms are tremors, tachycardia, nervousness, insomnia, sweating and shortness of breath. The preoperative patient anxiety level is in the category of severe, moderate. If it is not handled properly, it will have a negative impact on the operation process that will be carried out by the patient so that relaxation measures are needed so that the patient can control his anxiety. One recommended therapy is guided imagery. Various studies have been conducted to prove its effect. The objective of this research was to analyze effects of guided imagery towards anxiety level decrease on pre-operative patients. This research used literature review design, database used were 2018- 2020 Google Scholar. Research populations were all research journals regarding effects of guided imagery and progressive relaxation towards anxiety level decrease on pre-operative patients using flow diagrams technique (data synthesis) thus n-value was obtained = 3. Analyzed journals result showed that there was a decrease in anxiety level of pre-operative patients after guided was given. Guided imagery affected the decrease of anxiety level on pre-operative patients. Kecemasan merupakan reaksi psikologis yang dialami oleh sebagian besar pasien dalam menghadapi operasi. Hal ini ditandai dengan gerakan tremor, takikardi, gelisah, susah tidur, berkeringat dan sesak nafas. Kecemasan yang dirasakan oleh pasien pra-operasi berada pada kategori berat, sedang. Apabila tidak teratasi dengan baik, maka akan menimbulkan dampak negatif bagi proses operasi yang akan dijalankan pasien sehingga dibutuhkan tindakan norfarmakologi berupa pemberian tindakan rileksasi pada pasien agar pasien mampu mengontrol perasaan cemas yang dirasakannya. Salah satu terapi yang direkomendasikan adalah guided imagery. Berbagai penelitian telah dilakukan untuk membuktikan pengaruhnya. Tujuan penelitian ini adalah untuk menganalisis pengaruh guided imagery terhadap tingkat kecemasan pasien pra-operasi. Penelitian ini menggunakan desain literature review dengan jenis database yang digunakan, yaitu Google Scholar tahun 2018-2020. Populasi penelitian adalah seluruh jurnal penelitian tentang pengaruh terapi guided imagery terhadap tingkat kecemasan pasien pra-operasi dengan menggunakan teknik diagram flow (sintesis data) sehingga didapatkan n = 3. Hasil analisis jurnal penelitian menunjukan bahwa guided imagery efektif menurunkan kecemasan pasien pra-operasi.